Upper Airway Resistance Syndrome: An Underdiagnosed Sleep-related Breathing Disorder - Dennis Rafi; Larasati Budiyarto (Indonesian Society of Respirology (ISR), 2023)
Upper Airway Resistance Syndrome (UARS) is an example of a sleep-related breathing disorder. UARS was first reported by Guilleminault in 1992 and it is known as excessive daytime sleepiness without obvious apnea or hypopnea that is characterized by more than 50% of respiratory effort-related arousals (RERAs) during sleep. The prevalence of UARS was 15% in the population of São Paulo. Although clinical manifestations, electroencephalogram (EEG) findings, and pathogenesis differ between UARS and OSA (Obstructive Sleep Apnea), it still sparked a debate among researchers as to whether UARS should be categorized as a distinct disorder. The International Classification of Sleep Disorders - Third Edition (ICSD3) integrated UARS into OSA diagnosis, resulting in underdiagnosed and undertreated patients with sleep-related breathing disorders who did not necessarily meet OSA criteria. Untreated UARS, on the other hand, has a variety of clinical consequences, including poor weight and height growth, daytime irritability, worsening of quality of life, and cardiovascular complications. Continuous positive airway pressure therapy, oral appliances, surgical management, weight reduction, and positional therapy are all considered options in the management of UARS.